Characteristics and causes of forest and land fires in Kapuas District, Central Kalimantan Province, Indonesia - ACHMAD SIDDIK THOHA; BAMBANG HERO SAHARJO; RIZALDI BOER; MUHAMMAD ARDIANSYAH (Biodiversitas Journal of Biological Diversity, 2019)
Thoha AS, Saharjo BH, Boer R, Ardiansyah M. 2019. Characteristics and causes of forest and land fires in Kapuas District, Central Kalimantan Province, Indonesia. Biodiversitas 20: 110-117. Forest and land fire occurs almost every year in Indonesia. Its impact is very harmful for human and environment. Developing a program in fire management requires identification of forest and land fire characteristics and its causes. The aim of this research was to evaluate the characteristics and causes of forest and land fire in Kapuas District Central Kalimantan Province. Spatial analysis of hotspots with rainfall was used to determine temporal distribution of fire. Spatial distribution between hotspot and causative factors was determined to identify spatial characteristics of fires. Increasing number of hotspots occurs when monthly rainfall decreases. Most high fire activities are located in peatland, swamp shrubs, close to road, close to river and far away from villages. Fire causes from human activities mostly originated from swamp shrub burning and land clearing for farming. Hotspot density has various relationship with peat depth, land cover, accessibility, and human activities.